The reformation of feeling: shaping the religious emotions in early modern Germany - Karant-Nunn, Susan C. (Oxford University Press, 2010)
Catholic preaching -- The Lutheran churches -- The Reformed churches -- The Jews -- The Virgin Mary -- Dying and death -- Lay reception